A truncated intracellular Dicer-like molecule involves in antiviral immune recognition of oyster Crassostrea gigas. (March 2021) - Lv, Xiaojing; Wang, Weilin; Zhao, Qi; Qiao, Xue; Wang, Liyan; Yan, Yunchen; Han, Shuo; Liu, Zhaoqun; Wang, Lingling; Song, Linsheng
Abstract: The enzyme Dicer is best known for its role as an endoribonuclease in the small RNA pathway, playing a crucial role in recognizing viral double-stranded RNA (dsRNA) and inducing down-stream cascades to mediate anti-virus immunity. In the present study, a truncated Dicer-like gene was identified from oyster Crassostrea gigas, and its open reading frame (ORF) encoded a polypeptide (designed as Cg DCL) of 530 amino acids. The Cg DCL contained one N-terminal DEAD domain and a C-terminal helicase domain, but lack the conserved PAZ domain, ribonuclease domain (RIBOc) and dsRNA binding domain. The mRNA transcripts of Cg DCL were detected in all the examined tissues with high expression levels in lip, gills and haemocytes, which were 62.06-fold, 48.91-fold and 47.13-fold ( p < 0.05) of that in mantle, respectively. In the primarily cultured oyster haemocytes, the mRNA transcripts of Cg DCL were significantly induced at 12 h after poly(I:C) stimulation, which were 4.04-fold ( p < 0.05) of that in control group. The expression level of Cg DCL mRNA in haemocytes was up-regulated significantly after dsRNA and recombinant interferon-like protein (r Cg IFNLP) injection, which was 12.87-fold ( p < 0.01) and 3.22-fold ( p < 0.05) of that in control group, respectively. Cg DCL proteins were mainly distributed in the cytoplasm of haemocytes. The recombinant Cg DCL protein displayed binding activity to dsRNA and poly(I:C), but no obvious dsRNA cleavage activity. These results collectively suggest that truncated Cg DCL from C. gigas was able to be activated by poly(I:C), dsRNA and Cg IFNLP, and functioned as an intracellular recognition molecule to bind nucleic acid of virus, indicating a potential mutual cooperation between RNAi and IFN-like system in anti-virus immunity of oysters. Highlights: A truncated form of Dicer was identified from oyster. Cg DCL mRNA expression was induced by stimulation of dsRNA, poly(I:C) and Cg IFNLP. r Cg DCL exhibited binding activity to poly(I:C) and dsRNA while no dsRNA cleavage activity.